Taxonomic revision of the Malagasy Camponotus subgenus Mayria Hymenoptera, Formicidae) using qualitative and quantitative morphology - Rakotonirina, Jean Claude; Fisher, Brian L. (Zootaxa, 2018)
The Camponotus subgenus Mayria is revised based on the analysis of both qualitative morphological characters and morphometric traits. The multivariate analysis combined the Nest Centroid (NC)-clustering method and Partitioning Algorithm based on Recursive Thresholding (PART) function to generate species hypotheses based on 19 continuous morphological traits of minor workers. The proposed species hypotheses were confirmed by cumulative Linear Discriminant Analysis (LDA). Morphometric ratios for the subsets of minor and major workers were used in species descriptions and redefinitions. In this study, 14 species are recognized, of which seven are newly described: C. lamosy sp. n., C. liandia sp. n., C. mainty sp. n., C. manabo sp. n., C. raina sp. n., C. sada sp. n., C. tanosy sp. n. Four species are redescribed: C. christi Forel, C. dromedarius Forel, C. lubbocki Forel, and C. repens Forel. The following are raised to species and redescribed: C. foersteri Forel stat. n., C. maculiventris Emery stat. n., and C. pulcher stat. n. The following are synonymized under C. foersteri: Camponotus cambouei Forel, syn. n.; C. christi ambustus Forel, syn. n.; C. christi ferrugineus Emery, syn. n. and C. pictipes Forel, syn. n. The following are synonymized under C. lubbocki: Camponotus lubbocki christoides Forel, syn. n. and C. lubbocki rectus Forel, syn. n. Also included in this revision are an illustrated species identification key, taxonomic discussions, images, and distribution maps for each species superimposed with the ecoregions of Madagascar.